Slay in character - Cahoon, Lynn (Cahoon, Lynn. Cat Latimer mystery., 2018)
Cat and the members of her writers<U+2019> retreat have just arrived in Outlaw, Colorado, an “Old West” tourist town complete with inhabitants dressed up as famous figures from history. But this authentic slice of Americana takes a murderous turn when a college student masquerading as a 19th-century saloon girl becomes history herself. Was she the intended target? Or did she take a hit meant for someone else? With a cast of suspects to choose from<U+2014>including some notorious gunslingers and the sleazy town founders<U+2014>Cat must unhorse the real culprit before a real-life ghost story is given a killer twist . . .